What empiric treatment should be given for suspected bacterial keratitis in Northern Italy?. Issue 6 (November 2022) - Romano, Vito; Bignotti, Stefano; Forbice, Eliana; Piccinelli, Giorgio; Caruso, Arnaldo; Semeraro, Francesco
There is a lack of epidemiological studies reporting bacteria profiles, susceptibility, and suggested empiric (first line) treatment in Northern Italy. Our internal audit of corneal scraping for microbial keratitis at University of Brescia reports 116 bacterial strains isolated between January 1, 2013, and December 31, 2020. All cases had at least an epithelial defect of 1 mm in diameter. 36.2% (42) were Gram-positive, while 63.7% (74) Gram negative. In our results Gram-negatives are sensitive to ciprofloxacin in 94.5% and Pseudomonas in 95%. Grampositives are sensitive to teicoplanin in 91, 1%. Those data may help to establish empiric treatment in case of bacterial keratitis.